Judge Frank Creede, Jr. Swears In Superior Court Judge Mario Olmos - Watkins, Howard::::::::: (1983)
Judge Frank Creede, Jr. talking with Judge Mario Olmos; Mary Louise Frampton holding Margaret Olmos, Daniel Olmos, Delores Olmos and Fidel Olmos Law Offices of Olmos and Frampton at 925 N St. #150, Fresno